(untitled) (UNED Research Journal, 2018)
Compost is a bio-fertilizer that contains nutrients, organic matter, water and microorganisms that benefit the integrity of agroecosystems. Compost quality is highly dependent on the characteristics of the materials employed in production. One of the main challenges in compost technology is quality optimization. MM are microbial cultures containing dense populations of native soil microorganisms including bacteria, fungi and actinomycetes. LDBIO are the precipitated solids found in anaerobic reactors. This is a low cost, non-experimental, economic, low resolution pre-feasibility study that uses robust laboratory analytical methods to identify whether these compounds can be used as compost optimization agents, and identify the combination of these materials that produce the highest quality compost. According the results obtained, there is empirical evidence that MM and LDBIO have potential as compost optimization agents. The compost with the best quality characteristics (macronutrient concentration, organic matter, carbon and water content, microbial biomass) is the one that contains both MM and LDBIO. The incorporation of these materials in the compost does not affect other compost quality parameters such as pH, EC and C/N ratio. It does not affect the maturity, stability and innocuity of compost. Therefore, at this level of resolution, it is concluded that it is feasible to continue researching these materials as compost optimization agents. It is recommended to implement plant growth-response tests in order to identify the potential of the optimized compost to enhance plant development.